Loss of Kex2 Affects the Candida albicans Cell Wall and Interaction with Innate Immune Cells - Manuela Gómez-Gaviria (Journal of Fungi, 2020)
The secretory pathway in Candida albicans involves the protein translocation into the lumen of the endoplasmic reticulum and transport to the Golgi complex, where proteins undergo posttranslational modifications, including glycosylation and proteolysis. The Golgi-resident Kex2 protease is involved in such processing and disruption of its encoding gene affected virulence and dimorphism. These previous studies were performed using cells without URA3 or with URA3 ectopically placed into the KEX2 locus. Since these conditions are known to affect the cellular fitness and the host–fungus interaction, here we generated a kex2Δ null mutant strain with URA3 placed into the neutral locus RPS1. The characterization of this strain showed defects in the cell wall composition, with a reduction in the N-linked mannan content, and the increment in the levels of O-linked mannans, chitin, and β-glucans. The defects in the mannan content are likely linked to changes in Golgi-resident enzymes, as the α-1,2-mannosyltransferase and α-1,6-mannosyltransferase activities were incremented and reduced, respectively. The mutant cells also showed reduced ability to stimulate cytokine production and phagocytosis by human mononuclear cells and macrophages, respectively. Collectively, these data showed that loss of Kex2 affected the cell wall composition, the protein glycosylation pathways, and interaction with innate immune cells.